International Business - Daniel P. Sullivan; John D. Daniels; Lee H. Radebaugh; Prashant Salwan (Noida, 2024)
Balancing authoritative theory and meaningful practice, International Business engages students on the subject of conducting business in international markets. The authors' descriptions and ideas of international business are enhanced with contemporary examples, scenarios, and cases that help students effectively apply what they've learned. Now in its 16th Edition, International Business remains one of the best-selling and most authoritative international business texts available. As rigorous and practical as ever, this edition remains up-to-date through updated or newly written cases, streamlined writing, and expanded coverage of relevant global changes."
English
Keywords: International Business; Management